1992
DOI: 10.1093/oxfordjournals.humrep.a137542
|View full text |Cite
|
Sign up to set email alerts
|

SHORT COMMUNICATION: The cumulative embryo score: a predictive embryo scoring technique to select the optimal number of embryos to transfer in an in-vitro fertilization and embryo transfer programme

Abstract: In order to achieve a clinical pregnancy rate higher than that achieved following initial adoption of in-vitro fertilization embryo transfers, more than one embryo is transferred. This has led to a substantial increase in unwanted multiple pregnancy rates with IVF as compared with natural conception. What is therefore required is a simple, clinically useful embryo scoring system, to reflect embryo developmental potential, which will enable the selection of the optimal number of embryos to transfer in order to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
204
1
21

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 495 publications
(228 citation statements)
references
References 6 publications
2
204
1
21
Order By: Relevance
“…It is unclear, however, if GnRH agonist use results in comparable pregnancy rates. For example, one study found that GnRH agonist use resulted in significantly lower implantation and clinical pregnancy rates, in addition to a significantly higher rate of early pregnancy loss, than observed with hCG, with these differences likely due to luteal phase deficiency [9]. The likelihood of live births was improved after GnRH use in frozenthawed embryo replacement cycles, further suggesting that GnRH agonist triggering is accompanied by luteal phase deficiency [10,11].…”
Section: Dıscussıonmentioning
confidence: 99%
“…It is unclear, however, if GnRH agonist use results in comparable pregnancy rates. For example, one study found that GnRH agonist use resulted in significantly lower implantation and clinical pregnancy rates, in addition to a significantly higher rate of early pregnancy loss, than observed with hCG, with these differences likely due to luteal phase deficiency [9]. The likelihood of live births was improved after GnRH use in frozenthawed embryo replacement cycles, further suggesting that GnRH agonist triggering is accompanied by luteal phase deficiency [10,11].…”
Section: Dıscussıonmentioning
confidence: 99%
“…Currently, assessment of embryo morphology remains the choice of method. The correlation between developmental potential and morphological parameters, such as the degree of fragmentation, presence and number of nuclei and size, number and symmetry of blastomeres per embryo at distinct inspection points is well-established [12,31,33,36,39,43]. Present morphological evaluation, however, requires inspection outside the controlled environment of the incubator, which exposes the embryos to undesirable changes in critical parameters: temperature, humidity and pH when evaluated [42].…”
Section: Introductionmentioning
confidence: 99%
“…As other groups (6,7,48,49), we have proposed a modified cumulative embryo score (35,50) from PN evaluation until day transfer. Following such criterion the embryo selected to be transferred (top quality embryo) must feature good PN morphology (S0), two cells at 26 h after ICSI, and also be classified as "good quality" on day 3.…”
Section: Discussionmentioning
confidence: 99%